Properties of a Recombinant Chimeric Protein in which the gamma-Carboxyglutamic Acid and Helical Stack Domains of Human Anticoagulant Protein C Are Replaced by those of Human Coagulation Factor VII - Geng, Jie-Ping; Castellino, Francis J (Thrombosis and Haemostasis, 1997)
A chimeric cDNA, encoding residues 1-46 (the γ-carboxyglutamic acid module and its trailing helical stack) of human coagulant factor (f) VII, bound to residues 47-419 of human anticoagulant protein C (PC), was constructed and expressed. The resulting protein, r-[∆GD-HSPC/∇GD-HSfVII]PC, was properly processed with regard to signal/ propeptide release, cleavage of the K156R dipeptide, Gla and Hya contents, and the presence of glycosylation.The mutant protein displayed normal dependencies on Ca2+ for adoption of its metal ion-dependent conformation and for binding to acidic phospholipid vesicles. The chimera failed to recognize a monoclonal antibody (MAb) specific for the Ca2+-induced conformation of the Gla domain (GD) of PC, but did react with another MAb directed in part to the Ca2+-dependent conformation of the GD of fVII. Further, this chimeric protein possessed similar steady state constants as wild-type r-PC toward activation by thrombin and thrombin/thrombomodulin. The activated form of the chimera was very similar to that of its wild- type counterpart in its whole plasma anticoagulant activity, as well as its activity toward inactivation of coagulation factor VIII. The chimeric protein did not bind to the fVII cofactor, tissue factor, showing that the GD/HS domain region of fVII is insufficient for that particular interaction.The results demonstrate that the GD/HS of fVII, when present in the PC and APC background, serves to maintain the Ca2+/PL-related functions of these latter proteins, and suggest that the Ca2+ and PL- dependent interactions of the GD-HS of PC are sufficiently general in nature such that the GD-HS regions of other proteins of this type can satisfy most of the requirements of PC and APC. The data presented also offer support for the independent nature of the domain unit consisting of the GD/HS module.